Early Changes in Corneal Epithelial Thickness after Cataract Surgery – Pilot Study. (3rd March 2016) - Calabuig-Goena, María; López-Miguel, Alberto; Marqués-Fernández, Victoria; Coco-Martín, María B.; Iglesias-Cortiñas, Darío; Maldonado, Miguel J.
Abstract: Purpose : To assess early variations in central and paracentral corneal epithelial and non-epithelial thicknesses after uneventful clear corneal incision phacoemulsification. Materials and Methods : Twenty patients with a senile cataract underwent coaxial phacoemulsification through a 2.75-mm-wide corneal incision created at 180° in a prospective cohort pilot study. Corneal sublayer thickness measurements were obtained with Fourier-domain optical coherence tomography (FD-OCT, Cirrus HD-OCT, Carl Zeiss Meditec, Inc., Dublin, CA) before and after 1 week and 1 month postoperatively. Central measurements were performed in the middle of the FD-OCT scan and in the 3-mm corneal diameter (paracentral 180° and 0° locations). Epithelial, non-epithelial and total corneal pachymetry were measured at the central and paracentral locations. Results : No significant changes in epithelial thickness were seen 1 week postoperatively. However, 1 month postoperatively, the central, 180°, and 0° paracentral epithelial thicknesses (52.7 ± 3.8, 53.1 ± 5.4, and 52.7 ± 5.3 µm, respectively) decreased significantly ( p  < 0.01) compared to preoperatively (57.2 ± 4.8, 58.0 ± 5.7, 56.6 ± 5.3 µm, respectively). The 1-week central, 180°, and 0° paracentral non-epithelial corneal thicknesses (515.5 ± 39.6, 534.3 ± 45.6, and 521.3 ± 36.9 µm) were significantly ( p  < 0.01) higher than preoperatively (486.2 ± 34.7, 498.2 ± 33.8, 497.5 ± 32.3 µm, respectively). The non-epithelial corneal thickness increase was significantly ( p =  0.02) greater after 1 week in the central (29.3 ± 17.2 µm) and the 180° paracentral (36.1 ± 28.7 µm) locations than at the 0° paracentral location (23.8 ± 16.5 µm). Conclusions : Immediate postoperative corneal edema following phacoemulsification irregularly affects the cornea at the sublayer level. The initial central and paracentral non-epithelial thickening is compensated by subsequent central and paracentral epithelial thinning. These initial changes occurred more markedly closest to the main incision over the entrance pupil, which may have visual implications.